Good girl, bad boy: Corrupt behavior in professional tennis (2015)
This paper identifies matches on the male and female professional tennis tours in which one player faces a high payoff from being “on the bubble” of direct entry into one of the lucrative Grand Slam tournaments, while their opposition does not. Analyzing over 378,000 matches provides strong evidence for corrupt behavior on the men’s tour, as bubble players are substantially more likely to beat better ranked opponents when a win is desperately needed. However, we find no such evidence on the women’s tour. These results prevail throughout a series of extensions and robustness checks, highlighting gender differences regarding corrupt and unethical behavior, but also concerning collusion. We especially find evidence for collusion once monetary incentives are further increased. Finally, the market for sports betting does not seem to be aware of this phenomenon, suggesting a market imperfection and further confirming our suspicion of irregular activities in men’s tennis.